A multispeaker dataset of raw and reconstructed speech production real-time MRI video and 3D volumetric images - Yongwan Lim (Nature Portfolio, 2021)
Measurement(s) Speech • vocal tract Technology Type(s) magnetic resonance imaging Factor Type(s) age • sex • native/non-native speaker Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14892921